Discovery of antigens and cellular mechanisms in the protozoan parasite sarcocystis aucheniae using immunoproteomics - Wieser, Sara Nathaly; Decker Franco, Cecilia; De Alba, Paloma; Romero, Sandra Raquel; Ferrari, Alejandro; Schnittger, Leonhard; Florin-Christensen, Monica (MDPI, 2024)
Sarcocystis aucheniae is a coccidian parasite that produces macroscopic sarcocysts in South American camelid (SAC) muscles and causes a disease known as SAC sarcocystosis. This parasitosis hampers the commercialization of llama and alpaca meat, a vital economic activity in the Andean regions. No control or prevention methods are available, and diagnosis is based on postmortem visual inspection of carcasses. The aim of this study was to identify S. aucheniae B-cell epitopes suitable for the development of diagnostic methods for SAC sarcocystosis. To this end, sarcocyst immunoreactive protein bands were analyzed via mass spectrometry, and proteins in each band were identified in silico by searching in the parasite transcriptome. Five highly antigenic, hydrophilic B-cell epitopes, predicted not to cross-react with antibodies against other coccidia, were selected for future development of peptide-based serological tests. In addition, conserved domains present in the identified proteins allowed us to unravel metabolic pathways and mechanisms active in the parasitic stages present in sarcocysts, including aerobic respiration, antioxidant activity, signal transduction, protein synthesis and processing, and host–pathogen interactions. This study provides novel information on the biology of S. aucheniae, as well as new protein sequences that can be used for the development of diagnostic tests and chemotherapeutic approaches for SAC sarcocystosis.